Noise-tolerance consensus formation control for multi-robotic networks. (May 2020) - Wang, Chuangchuang; He, Ping; Li, Heng; Tian, Jinyu; Wang, Kuiyang; Li, Yangmin
This paper investigates the formation control for noise-tolerance consensus of multi-robotic networks and the mean square consensus condition. Firstly, the multi-robot model is expressed by applying a coordinate transformation based on the Euler-Lagrange equation. Compared with recent works, the control scheme presented in this work can indirectly obtain the evolution trend of position and velocity information of the robot. Besides, the noise and communication delay are involved in the formation control protocol. Secondly, the sufficient conditions of mean square consensus for formation control in multi-robotic networks with communication delay under noisy environments are obtained by using linear matrix inequality schemes. Finally, the numerical simulations are presented and submitted to demonstrate the correctness of the obtained results.